fx-gx=hforx

Simple and best practice solution for fx-gx=hforx equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for fx-gx=hforx equation:


Simplifying
fx + -1gx = hforx

Solving
fx + -1gx = fhorx

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-1fhorx' to each side of the equation.
fx + -1fhorx + -1gx = fhorx + -1fhorx

Reorder the terms:
-1fhorx + fx + -1gx = fhorx + -1fhorx

Combine like terms: fhorx + -1fhorx = 0
-1fhorx + fx + -1gx = 0

Add 'gx' to each side of the equation.
-1fhorx + fx + -1gx + gx = 0 + gx

Combine like terms: -1gx + gx = 0
-1fhorx + fx + 0 = 0 + gx
-1fhorx + fx = 0 + gx
Remove the zero:
-1fhorx + fx = gx

Combine like terms: gx + -1gx = 0
-1fhorx + fx + -1gx = 0

Factor out the Greatest Common Factor (GCF), 'x'.
x(-1fhor + f + -1g) = 0

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing f to the left, all other terms to the right. Add '-1x' to each side of the equation. x + -1x = 0 + -1x Remove the zero: 0 = -1x Simplifying 0 = -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-1fhor + f + -1g)' equal to zero and attempt to solve: Simplifying -1fhor + f + -1g = 0 Reorder the terms: f + -1fhor + -1g = 0 Solving f + -1fhor + -1g = 0 Move all terms containing f to the left, all other terms to the right. Add 'g' to each side of the equation. f + -1fhor + -1g + g = 0 + g Combine like terms: -1g + g = 0 f + -1fhor + 0 = 0 + g f + -1fhor = 0 + g Remove the zero: f + -1fhor = g The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 3(x+4)+x=(2x-7) | | -2x+2+3x=6 | | 7p-(p+4)=-2(2p-1)+10 | | 3-x+4x=6 | | 5+7x-x=71 | | X+1.5x= | | 7x-7y=5solvey | | 4nsquared+4n-168=0 | | k=gd | | 21x+1=4 | | 6m+6(6m-3)=108 | | 10-5t=6t-23 | | f(x)=ln(e^2x) | | y+3=.5(x-4) | | 16y^8= | | 3x+84=75 | | 72x+9y=18 | | 13x=2(5x+3) | | 9(x+7)+10=11x-2(x-3) | | 24-2x=14x-21 | | 3x^3+8x=420 | | 5b^4=134 | | 5+3(3x-5)=5-4(2x+1) | | 3x^2+8x=420 | | 2cosx=1-sinx | | f(x)=x^3-3x^2-9x+12 | | 0.8(x+300)=0.84x-56 | | 14-x^4= | | 2cos^2x+2cosx-1=0 | | 0.87y+2=y-0.6 | | 23.4=7.8*n | | (k-4)x^2-3kx-k-1=0 |

Equations solver categories